The Cultural Pragmatics of Silence: A Cross Cultural Corpus and Experimental Study of Unfilled Pauses in High vs. Low Context Societies - Muhammad Ridwan; Belay Sitotaw Goshu (Britain International for Academic Research (BIAR-Publisher), 2026)
Silence in conversation is a pragmatic resource whose interpretation varies across cultures. Hall’s (1976) high‑context (HC) versus low‑context (LC) framework predicts that HC cultures value silence as respectful and reflective, whereas LC cultures perceive it as awkward or evasive. Empirical evidence linking unfilled pause duration to Hall’s dimension remains scarce. This study examined cross‑cultural differences in the production and interpretation of unfilled pauses. We tested whether HC speakers produce longer, more frequent pauses and whether listeners from HC versus LC cultures differentially rate willingness, politeness, and competence as a function of pause length. Phase 1 analysed naturalistic corpora (Japanese, Egyptian Arabic, German, American English; N = 400 conversations). Phase 2 used a controlled experiment (N = 480) with four pause durations (0.2–2.5 s) across two speech acts. HC speakers produced pauses nearly twice as long and frequent as LC speakers. Experimentally, LC listeners showed a steep decline in willingness ratings with longer pauses (52% drop), while HC listeners showed only a shallow decline (15%). A significant interaction emerged for politeness: longer pauses increased politeness for HC listeners but decreased it for LC listeners. Silence operates as a culturally variable pragmatic marker, supporting Hall’s framework and challenging Universalist accounts. Intercultural training should address pause‑norm differences; language assessment should include pragmatic competence regarding unfilled pauses.